Uncovering the links between climate adaptation policy, science and practice - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
A new research project by the International Livestock Research Institute (ILRI) will be looking at the linkages between climate adaptation and livestock science, policy and practice. The three-year project is part of the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) Flagship on Policies and Institutions for Climate-Resilient Food Systems, and here further introduced by project leaders Todd Crane and Lance Robinson.